Pemanfaatan Eco Enzyme sebagai Upaya Pereduksi Limbah Organik di Desa Sumput, Kota Sidoarjo - Budi Prabowo; Khusnul Mubarok; Alvin Adrian Wibisono; Riko Ferdinand Abdillah; Aldy Syahputra; Naufal Kensadiharja (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Organic waste remains a significant problem in various major cities in Indonesia, especially in urban areas such as Jakarta, Bandung, and Surabaya. Household waste, which predominantly consists of organic materials, is often simply discarded or burned without proper processing, leading to environmental issues. One innovative solution that is beginning to be implemented is the processing of organic waste into eco enzyme. Eco enzyme is a versatile liquid produced through the fermentation of organic waste, such as vegetable and fruit scraps. This study aims to examine the process of making eco enzyme and its benefits for both society and the environment. The research method involves several stages, starting from material preparation, the fermentation process, to the harvesting of eco enzyme. The results of the study indicate that eco enzyme products offer various benefits, including as a natural cleaner, organic fertilizer, and a substance for improving air and soil quality. The three-month fermentation process produces eco enzyme with a fresh acidic smell and a pH below 4. Additionally, eco enzyme can be utilized on a household scale up to a larger scale for agricultural and environmental management purposes. Although eco enzyme has great potential in waste management, the main challenges faced are the lack of awareness and knowledge among the community regarding the benefits and production methods of eco enzyme. Therefore, further efforts in socialization and training are needed to maximize the potential of eco enzyme as a sustainable solution in organic waste management.